Pemanfaatan Aplikasi Meeting Daring Zoom Pada Anak Sekolah Di Perumahan Griya Duren Tuntungan - Abdul Sani Sembiring (STMIK Budi Darma, 2022)
One of the effects of Covid-19 that has attacked Indonesia, especially in the field of education, is that it requires learning to be carried out using distance learning media. One of these distance learning media is the Zoom online meeting application. Many school children do not understand how to use the features provided in the Zoom application. The provision of information on the use of the features that exist in the zoom is still considered very lacking for school children in general, considering that these school children cannot directly receive training on the use and utilization of the application. Zoom meet is a face-to-face conference platform where educators and students can interact directly like meeting in person in class. In this application there are many features provided and offer the easiest facilities for individuals who want to join.